MALNUTRITION RISK FACTORS BASED ON SLEEP DURATION AND PHYSICAL ACTIVITY: STUDIES IN BANGLADESH AND INDONESIA - Catur Wulandari; Anugrah Linda Mutiarani; Pratiwi Hariyani Putri; Sa’bania Hari Raharjeng (Universitas Airlangga, 2026)
Introduction: Indonesia faces a